1995
DOI: 10.1074/jbc.270.5.2036
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for p21 Activation in the Metabolic Signaling by Insulin

Abstract: To evaluate the role of the "Ras pathway" in mediating metabolic signaling by insulin, we employed lovastatin to exhibit isoprenilation of Ras proteins in Rat-1 fibroblasts transfected with human insulin receptors (HIRc cells) and in differentiated 3T3-L1 adipocytes. Lovastatin blocked an ability of insulin to activate p21ras and mitogen-activated protein kinase. Lovastatin also significantly (p < 0.01) reduced insulin effects on thymidine incorporation and glucose incorporation into glycogen. Nevertheless, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Lovastatin, however, was added 24 h prior to insulin addition. It has previously been shown that shorter preincubation times with lovastatin had little to no effect on the insulin-stimulated MAP kinase activity (22,43). RNA Isolation and Northern Analysis-Total RNA was extracted using the guanidinium isothiocyanate method described by Chomczynski and Sacchi (45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lovastatin, however, was added 24 h prior to insulin addition. It has previously been shown that shorter preincubation times with lovastatin had little to no effect on the insulin-stimulated MAP kinase activity (22,43). RNA Isolation and Northern Analysis-Total RNA was extracted using the guanidinium isothiocyanate method described by Chomczynski and Sacchi (45).…”
Section: Methodsmentioning
confidence: 99%
“…Once activated by phosphorylation, the Shc proteins associate with various downstream effector molecules including Grb2 and the guanine nucleotide-releasing factor (21). Grb2/SOS interaction plays a role in the insulin activation of Ras, since SOS facilitates the exchange of GDP for GTP on Ras proteins (22).…”
mentioning
confidence: 99%
“…Activated FOXO1 induces Npy transcription and represses Pomc expression, while inhibitory phosphorylation of FOXO1 causes its translocation out of the nucleus, resulting in increased Pomc mRNA and decreased Npy mRNA levels (Kim et al 2006, Kitamura et al 2006, Plum et al 2006a. Insulin signal transduction also stimulates the MAPK pathway leading to mitogenesis (Reusch et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This could suggest that the TSH stimulation of the mevalonate biosynthetic pathway could be required for the TSH-induced proliferation of these cells. To test this hypothesis, we have investigated the effect of lovastatin, an HMG-CoA reductase inhibitor (14,15), on protein or DNA synthesis induced by insulin or TSH.…”
Section: Introductionmentioning
confidence: 99%